Performance Analysis of Inpatient Unit at Universitas Indonesia Hospital Using the Malcolm Baldrige Framework in 2024 - Ambarwati, Maulaya Istafa Tiwikrama; Basabih, Masyitoh; Sultoni, Siti (Universitas Muhammadiyah Yogyakarta, 2026)
The increasing number of hospitals each year has intensified competition. Hospitals must continuously improve their performance to survive and remain competitive. Inpatient performance assessment can help achieve more optimal results, as it represents the largest contributor to hospital revenue. This study aims to obtain results from an inpatient performance analysis using the Baldrige Excellence Framework at the Universitas Indonesia Hospital in 2024. This study used a cross-sectional design with a quantitative approach to obtain perceptions of performance assessment from the employee's perspective. The research sample was recruited using convenience sampling, comprising 58 respondents. This research reveals that the highest percentage index is the measurement, analysis, and knowledge management category (78,1%), while the lowest is the workforce category (70,8%). Bivariate analysis results uncover that the strategy category (r = 0.437) has a moderate correlation with result, while the other five categories have strong correlations: leadership (r = 0.572), customers (r = 0.640), measurement, analysis, and knowledge management (r = 0.716), workforce (r = 0.683), and operations (r = 0.630). Result category is influenced by suboptimal workforce management, including recruitment systems, allocation, planning, engagement, incentives, rewards, and efforts to prevent workforce reductions driven by high turnover. Management needs to place greater focus on the workforce by aligning with the characteristics of Generation Z, which currently dominates the workforce, to achieve better performance.